Human Morality and Sustainability: Insights from The Divine Comedy of Dante Alighieri - Whitmore, Lawrence (European Journal of Sustainable Development, 2024)
In this paper it is argued that the root cause of the environmental crisis is the moral condition of mankind. Over-indulgence, over-consumption and a desire for material wealth and possessions, far in excess of what is needed for survival and comfort, callous use of technology to overexploit the land and seas for profit, lack of diligence in addressing threats to the environment, and the tendency towards aggressive conflict, all contribute towards the decimation of natural eco-systems. Moral improvement is therefore considered as a possible pathway towards sustainability. The impact of human morality upon the environment is examined using the system of capital vices and virtues. Particular reference is given to The Divine Comedy of Dante Alighieri, which provides profound insight into the human condition. The capital vices are shown to play a significant part in the decline of the environment by driving mankind’s overconsumption and overindulgence, while cultivation of the capital virtues is shown to provide a pathway of moral improvement allowing human beings to live responsibly and in greater harmony with the planet. Embracing these moral virtues can provide a necessary course correction for human beings today so that we can build upon the successes of our past and thrive as one species sharing the planet with other species and securing a sustainable future. Keywords: morality, ethics, sustainable development, The Divine Comedy, moral philosophy.